'WRITING LABORATORY': A POST-REFORMATION DOMINANT IDEOLOGY OF INDONESIAN STUDENTS PRESS Critical Discourse Analysis of The Discourse of ‘Pers Mahasiswa’ in Poros Ahmad Dahlan University (UAD) Yogyakarta Student Press Organisation - Canny Sylvia; Holy Rafika Dhona (Department of Communications, Universitas Islam Indonesia, 2018)
This article explain the dominant ideology shaped of contemporary Indonesian student press. The study took the banning of Poros, Ahmad Dahlan University's Students Press in 2016, as the case. By using a three-dimensional analysis of Fairclough's critical discourse analysis, this paper questions three things; what is the dominant ideology of the student press represented in the text? How is this dominant ideology also shape the process of producing text? How does the ideology relate to the socio-cultural history of the Indonesian student press? This study found that the dominant ideology of contemporary students press was a 'journalism laboratory', which was actually an extension of the New Order's program to de-politising Indonesian student movement.Keywords: ideology, student press, discourse, Fairclough.